2014
DOI: 10.4104/pcrj.2014.00008
|View full text |Cite
|
Sign up to set email alerts
|

Wheezing phenotypes in young children: an historical cohort study

Abstract: Background: Wheezing phenotypes in young children have usually been described on the basis of questionnaire surveys instead of prospectively doctor-diagnosed episodes, and have never been described in terms of incidence rates. Aims: To identify wheezing phenotypes in the first three years and describe their incidence trends, and to investigate their relationship with asthma at six years of age. Methods: Doctor-diagnosed wheezing episodes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…The prevalence of childhood wheezing is much higher than that of asthma, and it is difficult to know which "wheezers" have predilection for asthma. 70,71 Given the strong link between childhood wheezing and viral respiratory tract infection (due to smaller airway caliber and inflammation), wheezing could also act as a marker for increased risk of infection or for higher symptom severity when infected. 72 Four studies looked at both of these outcomes: Camargo et al 32 found a negative association (similar in size as well) between cord blood 25(OH)D and both wheeze and respiratory infection.…”
Section: Allergic Diseasementioning
confidence: 99%
“…The prevalence of childhood wheezing is much higher than that of asthma, and it is difficult to know which "wheezers" have predilection for asthma. 70,71 Given the strong link between childhood wheezing and viral respiratory tract infection (due to smaller airway caliber and inflammation), wheezing could also act as a marker for increased risk of infection or for higher symptom severity when infected. 72 Four studies looked at both of these outcomes: Camargo et al 32 found a negative association (similar in size as well) between cord blood 25(OH)D and both wheeze and respiratory infection.…”
Section: Allergic Diseasementioning
confidence: 99%
“…Wheezing during the first months of life might be associated with later asthma, especially when episodes are severe and/or frequent. 14 , 16 , 17 Time to the first episode of wheeze has been associated with the frequency of recurrence: the earlier the first episode occurs, the more frequently wheezing recurs. 18 It is possible that some environmental factors could influence the innate immune response during the first months of life, a critical period for immune system development, resulting in more frequent and severe episodes of wheezing.…”
Section: Introductionmentioning
confidence: 99%
“…29---31 Among the scarce evidence that may contribute to resolve this issue, we ought to highlight a Spanish community-based study of incident cases that identified a specific wheezing pattern consisting of a single episode typically occurring before age 13 months, with the incidence peak at 7 months. 32 On the other hand, both experts and clinical paediatricians agreed that AB is a term that should only be applied to a first episode. McConnochie 20 was the first to include this criterion in his definition of AB in 1983.…”
Section: Discussionmentioning
confidence: 99%